2022
DOI: 10.1111/nhs.12933
|View full text |Cite
|
Sign up to set email alerts
|

Patients' experiences of the decision‐making process for clinical trial participation

Abstract: Clinical decision-making about participating in a clinical trial is a complex process influenced by overwhelming information about prognosis, disease, and treatment options. The study aimed to explore patients' experiences of the decision-making process when patients are presented with the opportunity to participate in a cancer clinical trial and to shed light on how patients experience the health communication, the nurse's role, and the physician's role. A qualitative study design was applied. Nine patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…In agreement with other studies, we found that patients’ decisions to enrol in a clinical cancer trial were mostly influenced by emotions and trusting relationships with trial staff rather than engaging with often dense written information [ 7 , 10 , 15 ]. Some patients who found PICFs difficult to read viewed them as a legal formality and preferred learning about study information through verbal conversations with their trusted treating team.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with other studies, we found that patients’ decisions to enrol in a clinical cancer trial were mostly influenced by emotions and trusting relationships with trial staff rather than engaging with often dense written information [ 7 , 10 , 15 ]. Some patients who found PICFs difficult to read viewed them as a legal formality and preferred learning about study information through verbal conversations with their trusted treating team.…”
Section: Discussionsupporting
confidence: 92%
“…Physicians perceive themselves as responsible, 37,42,44,48 nurses experience physicians as having the leading role, 59,61 and people with cancer and their informal carers rely on and trust physicians to be the expert and know what is in their patients' best interests. [38][39][40][41]46,[48][49][50]56,57 Gregersen et al 46…”
Section: Comment (P 1184)mentioning
confidence: 99%
“…People with cancer and also health care professionals consider personal attributes such as experience, knowledge and communication skills as important for shared decision-making in palliative cancer care. 47,56,[59][60][61] Person-centred communication skills and the development of a trusting relationship are considered necessary to enable shared decision-making, 38,41,46,50,55,56,[60][61][62] as Lee et al 62…”
Section: (P302) Statesmentioning
confidence: 99%
See 2 more Smart Citations